Sensitive and specific modified Hodge test for KPC and metallo-beta- lactamase detection in Pseudomonas aeruginosa by use of a novel indicator strain, Klebsiella pneumoniae ATCC 700603 - Pasteran, Fernando (2011)
Fil: Pasteran, Fernando. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio de Antimicrobianos; Argentina.